ARAB-MANADO: JEJARING, KAPITALISME DAN IDENTITAS DI AWAL ABAD XX - Muhammad Nur Ichsan Azis; Kholili Badriza; Aziz Aziz; Syahril Siddik; Amorisa Wiratri (Jurnal Lektur Keagamaan, 2022)
ABSTRACT This paper aims to describe and analyze Arab Ethnic trading activities in Manado from 1899 to 1919 AD. The article employs a social science approach and historical methods to explore the networking activities, commodities, and the formation of Arab identity in Manado. Nusantara experienced a turning point in maritime trading activities around the 19th century to the 20th century. The commerce network had implications for commercial ports, communities, and identity groups in several strategic coastal areas, especially from 1899 to 1919. In Manado, Arab traders played important roles in commodity activities, especially rice, coffee, copra, and other agricultural products. Some of these roles are: being intermediary traders, commodity providers, Islamic preachers and educators in Manado and its surroundings. The modernization of Manado port in 1914 had affected the Manado Arab ethnic group. This situation urged the Arab change their orientation from economics to education to maintain themselves and their identity. Keywords: Arab Ethnic, Trading Network, Commodities.   ABSTRAK Tulisan ini bertujuan mendeskripsikan dan menganalisis aktivitas niaga etnis Arab di Manado selama tahun 1899-1919. Dengan menggunakan pendekatan ilmu sosial dan metode sejarah, kajian ini menunjukkan aktivitas jejaring, komoditas, dan pembentukan identitas etnis Arab di Manado. Nusantara mengalami titik balik dalam aktivitas niaga maritim sekitar akhir abad ke-19 hingga abad ke-20. Jejaring niaga berimplikasi pada bandar-bandar niaga, komunitas, dan kelompok identitias di beberapa kawasan pesisir strategis khususnya pada tahun 1899-1919 M. Di Manado, kalangan pedagang Arab berperan dalam perdagangan komoditas terutama beras, kopi, dan kopra, hingga hasil bumi. Salah satu peran tersebut adalah sebagai pedagang perantara dan penyedia komoditas hingga menjadi kelompok penyebar dan pengajar Islam di Manado dan sekitarnya. Modernisasi pelabuhan pada tahun 1914 di Manado berimplikasi besar bagi kalangan etnis Arab Manado. Mereka kemudian mengubah orientasi dari ekonomi ke pendidikan untuk mempertahankan diri dan identitas.  Kata kunci: Etnis Arab, Jejaring Niaga, Komoditas.